1989
DOI: 10.1111/j.1476-5381.1989.tb12679.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dihydropyridine compounds in behavioural tests of dopaminergic activity

Abstract: 1 The effects of the dihydropyridine calcium channel blocker nifedipine and the activator Bay K 8644 were investigated in different behavioural tests involving dopaminergic systems. These were the discriminative stimulus induced by amphetamine, rotational behaviour in rats with unilateral 6-hydroxydopamine (6-OHDA) lesions and apomorphine-induced yawning in rats. 2 The yawning induced by apomorphine (40 pg kg-s.c.) was significantly potentiated by nifedipine (5-10mgkg-'i.p.). Bay K 8644 (0.05-0.5mgkg-'i.p.) do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 27 publications
0
4
1
Order By: Relevance
“…The VAS and ARCI measures of subjective effect and the MCQ behavioral measure of reinforcement are those laboratory measures most predictive of abuse potential; therefore, we conclude that isradipine does not reduce cocaine's reinforcing effects in humans. These results are in contrast to preclinical data showing isradipine-related reductions in cocaine reinforcement (Kuzmin, Zvartau, Gessa, Martellotta, & Fratta, 1992; Martellotta et al, 1994) and dopamine release (Bourson et al, 1989; Pani et al, 1990). Whereas this suggests possible limitations of preclinical animal models, there also are limitations to the current clinical study model.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The VAS and ARCI measures of subjective effect and the MCQ behavioral measure of reinforcement are those laboratory measures most predictive of abuse potential; therefore, we conclude that isradipine does not reduce cocaine's reinforcing effects in humans. These results are in contrast to preclinical data showing isradipine-related reductions in cocaine reinforcement (Kuzmin, Zvartau, Gessa, Martellotta, & Fratta, 1992; Martellotta et al, 1994) and dopamine release (Bourson et al, 1989; Pani et al, 1990). Whereas this suggests possible limitations of preclinical animal models, there also are limitations to the current clinical study model.…”
Section: Discussioncontrasting
confidence: 99%
“…Preclinical studies have suggested that dihydropyridine-type calcium channel antagonists can antagonize dopamine release (Bourson, Gower, Mir, & Moser, 1989). Furthermore, microdialysis studies have shown that cocaine-induced increases in synaptic dopamine concentrations are blocked by two agents of the dihydropyridine class, isradipine and nimodipine, but not by other types of calcium antagonists (Pani et al, 1990).…”
mentioning
confidence: 99%
“…Instead, it produces a hypokinetic motor syndrome with dystonia [8]. BBay K 8644 exaggerates locomotor responses to cocaine, but does not exaggerate motor behaviors related to amphetamine [5,42]. Therefore, the hypothesis that BBay K 8644 provokes SB and SIB by stimulating a massive release of dopamine is likely to be oversimplified.…”
Section: Discussionmentioning
confidence: 99%
“…Group 14 and group 5 OVX animals were treated with Bay-K-8644 (0.05 mg/kg, i.p.). 15 Selected test and standard drug were administered for successive 40 days in-between 9 to 11 AM to avoid effect of fluctuating neuro-hormonal levels on the drugs. On 41 st day various parameters were studied like physical parameters of bone, blood chemistry, histopathological examination and osteoclast count were done.…”
Section: Animal Groupingmentioning
confidence: 99%